Investigation of stress-strain state in spinal model for various methods of surgical treatment of thoracolumbar burst fractures (Рart one) - Radchenko, Volodymyr; Popsuishapka, Kostiantin; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
There are different views on the treatment of burst fractures of the lower thoracic and lumbar spine. Some specialists prefer conservative methods of treatment, others use a spinal fusion of 360° (anterior and posterior). However, questions of the extent of fixation, its strength, the possibility of correction of deformation from the posterior approach, the feasibility of performing laminectomy, etc. are discussed. Objective: to create a finite element biomechanical model of an burst fracture of the ThXIIvertebra body in the ThIX–LVvertebra block and analyze the stress-strain state in different fixation types. Methods: three computational models of the ThIX–LVvertebra block were created with the destruction of 50 % of the body volume of the ThXIIvertebra and fixation: 1) ThIXand LV; 2) ThIX, ThXIIand LI; 3) ThX, ThXIand LI, LII, as well as variants of the model with destruction of vertebral pedicles. Results: with the vertical load, the posterior spinal column is the most stressed, and the maximum stresses (45.9–46.6 MPa) in the fixing structures are located in the rods. In the case of fixation by 6 screws, the stresses in the rods are reduced by approximately 20 % (to 37.7–38.1 MPa). With the use of 8 screws, the total stress level compared to the fixation of 4 and 6 screws significantly decreased, in particular in the block of vertebrae LI–LValmost twice. Damage to the posterior support complex in the form of vertebral arches fracture led to a significant increase in tension (by 17 %) in the injured vertebral body only in a model with 4 screws. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> the use of any transpedicular fixation leads to a decrease in stress in the damaged vertebra. With an increase in the number of screws in the fixing structure, the level of stresses decreases, but the pattern of their distribution in the spine does not change.